2024
DOI: 10.1021/acschemneuro.3c00754
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Dynamics of Amyloid Fibril Growth: Elongation and Lateral Assembly of GNNQQNY Protofibrils

Torsten John,
Aldo Rampioni,
David Poger
et al.

Abstract: The self-assembly of peptides and proteins into β-sheet rich amyloid fibrils is linked to both functional and pathological states. In this study, the growth of fibrillar structures of the short peptide GNNQQNY, a fragment from the yeast prion Sup35 protein, was examined. Molecular dynamics simulations were used to study alternative mechanisms of fibril growth, including elongation through binding of monomers as well as fibril self-assembly into larger, more mature structures. It was found that after binding, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…In particular, the Aβ(16–22) peptide was shown to form fibrils within a time frame of 2 μs using variants of the CHARMM36m force field, whereas fibrils did not form successfully using AMBER99SB-disp. , In another study, the amphipathic (FKFE) 2 peptide was shown to form a fibril using the AMBER99SB-ildn force field, and at high peptide concentrations, increasing temperature was shown to accelerate this process . In the same vein, simulations with a preformed fibril and a few peptides randomly located in the simulation box were used to study fibril growth and secondary nucleation . These studies are opening the door to our understanding of the sequence of molecular events leading to fibril formation.…”
Section: All-atom Simulationsmentioning
confidence: 97%
“…In particular, the Aβ(16–22) peptide was shown to form fibrils within a time frame of 2 μs using variants of the CHARMM36m force field, whereas fibrils did not form successfully using AMBER99SB-disp. , In another study, the amphipathic (FKFE) 2 peptide was shown to form a fibril using the AMBER99SB-ildn force field, and at high peptide concentrations, increasing temperature was shown to accelerate this process . In the same vein, simulations with a preformed fibril and a few peptides randomly located in the simulation box were used to study fibril growth and secondary nucleation . These studies are opening the door to our understanding of the sequence of molecular events leading to fibril formation.…”
Section: All-atom Simulationsmentioning
confidence: 97%